Chemical analysis of primary combustion products of boron-based fuel-rich propellants. Issue 123 (25th November 2015) - Liu, Lin-Lin; He, Guo-Qiang; Wang, Ying-Hong; Hu, Song-Qi
Abstract : The content of solid primary products of boron-based fuel-rich propellants could be determined quantitatively through the analysis procedure. Abstract : A facility was designed to collect the primary combustion products of boron-based fuel-rich propellants under different chamber pressures. The morphology and particle size of condensed-phase products were analyzed using a laser particle size analyzer and a scanning electron microscope (SEM), and chemical analysis of condensed-phase products was carried out by X-ray diffraction (XRD), laser Raman spectrometry, wet chemical analysis and elemental analysis. In addition, organics in condensed-phase products and gaseous products were analyzed by Fourier Transform Infrared Spectrometry (FTIR) and Gas Chromatography (GC), respectively. The results show that the condensed-phase products mainly consist of B, C, B4 C (or B12 C2 ), BN, Mg, MgO, MgAl2 O4, Al, Al2 O3, AlCl3, NH4 [Mg(H2 O)6 ]Cl3, NH4 Cl and Fe3 O4 ; there are large amounts of boron oxide and boron carbide in the condensed-phase products, which indicates that elemental boron is highly active during the primary combustion process; a higher chamber pressure may be disadvantageous to the secondary combustion efficiency because more inactive boron carbide, graphite and h-BN (especially boron carbide) are produced.